From Heritage To Commodity: The Politics Of Authenticity In Makassar’s Culinary Tourism - Muh Al Fatah Arief Putra; Andi Aryani Hardiyanti; Fitriani Rahim; Indah Lestari Anwar; Fakhirah Husain (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This study examines the cultural politics of culinary tourism in Makassar City, Indonesia, focusing on how ethnic cuisines function as both cultural representations and economic commodities. Employing a qualitative, interpretive approach grounded in cultural anthropology, the research analyzes secondary data from academic studies, tourism reports, and field observations to explore how authenticity, identity, and power intersect in Makassar’s evolving foodscape. The findings reveal that the city government and private stakeholders strategically promote dishes such as Coto Makassar, Pallubasa, Konro, and Pisang Epe as symbols of local heritage, while other traditional foods remain marginalized. This selective representation reflects institutional power in shaping narratives of authenticity and modernity. Culinary tourism in Makassar simultaneously preserves and commodifies cultural heritage, strengthening urban branding yet risking cultural simplification. Globalization, market adaptation, and the influence of food franchises such as Mie Gacoan further contribute to the homogenization of local cuisine. Nonetheless, local initiatives rooted in Bugis-Makassar culinary traditions continue to assert cultural resilience through the use of traditional ingredients and local wisdom. The study concludes that sustainable culinary tourism in Makassar requires inclusive governance and participatory cultural representation, ensuring that local communities maintain agency in defining their food heritage. Food, therefore, emerges as both sustenance and a medium for negotiating identity, power, and heritage in an increasingly globalized tourism economy.